International institutions and domestic pressures - Caraan, Aurea Dela Roca (KDI School, 2000)
This study aims to examine the Korean government trade policy decisionmaking process within the context of Philippine-Korean relations and international institutions, specifically, the WTO. It also analyzes the domestic and international pressures for and against trade liberalization affecting bilateral trade between the Philippines and Korea. Findings show that increased institutionalization has resulted in more liberalized trade between the Philippines and Korea from 1997 up to the present. Korea had to abandon certain restrictive trade policies after such policies had been found to be inconsistent with WTO rules. Persistent pressures from the Philippines and Korea's other Southeast Asian trading partners, including relative use of international norms, put the necessary pressure on the Korean government to change its trade policies. Findings further show that various domestic pressures affect bilateral trade. Korean interest groups either held up negotiations or advanced resolutions of issues, depending on how much influence they exerted. In general, how much impact various domestic groups have on the policy choices of Korea depends on the wider international negotiating environment rendered by the WTO. Although bilateral negotiations were stalled by domestic pressures in some cases, Korea made its decisions based on the binding rules of the WTO. Overall, the interplay among WTO norms and obligations, pressure from the Philippines and other foreign governments and pressure from domestic groups determine Korean government policy affecting trade with the Philippines.
Thesis(Master) --KDI School:Master of Public Policy,2000